Analysis of Oral Albumin Use and Factors Affecting the Success of its Therapy - Umi Fatma Wati (JURNAL FARMASI DAN MAKANAN, 2024)
Hypoalbuminemia is a risk factor for medical treatment. Albumin has been shown to be a predictor in a number of studies in various settings. Several studies examined albumin as a marker of nutritional status and its association with outcomes (eg, mortality and length of hospital stay). In critical illness, the Acute Physiology and Chronic Health Evaluation (APACHE III) risk score includes serum albumin levels and shows a strong inverse correlation between serum albumin and mortality in critically ill patients. This research was conducted observationally to analyze the use of oral albumin and the factors that influence the success of therapy in the Lung Inpatient Room at Dr Soetomo Regional Hospital for the period 1 January – 31 October 2022. Patients diagnosed with Community Pneumonia, Lung Cancer and Lung Tuberculosis. This research was carried out by collecting secondary data via e-medical records. Data taken were patient demographic data (name, gender, weight, age, length of stay) and albumin data before and after receiving oral albumin. From the research results, the number of samples was 87. The number of samples was 87 patients. Of the 87 patients, 66 male patients (75.86%) were 21 female patients (24.14%), the largest age range was 51 - 60 years, 21 patients (24.14%). The highest body weight ranged from 61-70 kg for 50 patients (57.47%), the longest length of stay ( Length of Stay ) was 10-20 days for 45 patients (51.72%). The most common primary diagnosis was new tuberculosis in 42 patients (48.28%). The highest use of oral albumin was more than 100 capsules, as many as 20 patients (22.99%) with the highest duration of use being 10-19 days, namely 38 patients (43.68%). The statistical results show that there is no significant difference between before receiving oral albumin and after receiving oral albumin with a value of P = 0.541. Factors that influence the success of oral albumin therapy are length of stay with a value of P = 0.001 * Keywords: Oral albumin, pulmonary tuberculosis, lung cancer, pneumonia, length of stay